2018
DOI: 10.5539/jfr.v7n4p30
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Traditional Meat Processing Knowledge among the Borana Pastoralist of Northern Kenya

Abstract: Indigenous knowledge on food preparation is an activity practised in almost all agricultural production system. Amongst the Borana pastoralist of Northern Kenya, milk and meat production are the cornerstone of livelihood, and more often abundance occurs without possibility of immediate consumption, triggering the need to preserve surplus for future consumption. The objective of this paper is to document and understand traditional meat preparation knowledge amongst Borana pastoralist’s women of Northern Kenya.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Traditional containers (locally referred to as Ebur in Turkana and Dhola/Dhibe/Subb in Marsabit) were made from sculptured wood with a leather bottom and lid; these retailed at between USD 2.0 and USD 10.0 depending on size, with the smallest having a capacity of about 250 ml and the largest having a capacity of 2 l. These containers were not washed; rather, they were sanitized by fumigation using smoke from Balanites rotundifolia locally known as Elamach or Adung in Turkana. Similar practices have been reported in previous research (Dabasso et al 2018;Gichure et al 2014).…”
Section: The Economic Dimension Of Human Well-being Within Slaughterhsupporting
confidence: 89%
See 1 more Smart Citation
“…Traditional containers (locally referred to as Ebur in Turkana and Dhola/Dhibe/Subb in Marsabit) were made from sculptured wood with a leather bottom and lid; these retailed at between USD 2.0 and USD 10.0 depending on size, with the smallest having a capacity of about 250 ml and the largest having a capacity of 2 l. These containers were not washed; rather, they were sanitized by fumigation using smoke from Balanites rotundifolia locally known as Elamach or Adung in Turkana. Similar practices have been reported in previous research (Dabasso et al 2018;Gichure et al 2014).…”
Section: The Economic Dimension Of Human Well-being Within Slaughterhsupporting
confidence: 89%
“…As reported in previous research, pastoral communities are increasingly diversifying their economic and social activities through value addition of meat and meat by-products, as well as engaging in crop farming, trade, and craftsmanship (Headey et al 2014;Rojas-Downing et al 2017). Cultural diversity during processing was observed among different communities which implies weakening or lost ties among pastoralists (Dabasso et al 2018;Gichure 2017).…”
Section: The Economic Dimension Of Human Well-being Within Slaughterhmentioning
confidence: 90%
“…The data in Table 2, also showed that the pH value of okara was 6.80 while the pH value of frozen meat was 5.50, The pH values of this study agreed with the values of pH obtained by Dabasso et al (2018) who indicated that the pH value was 5.71 in the thigh of beef while Ray et al(1984) found that the pH value was 5.6.…”
Section: Physicochemical Properties and Caloric Value Of Raw Materialsupporting
confidence: 88%
“…A combined methodology is considered to be very effective in conducting in-depth interviews and discussions for collecting the knowledge (data) on traditional food practices (40). In addition to personal interviews, participant observation was applied as a participatory tool with knowledge holders to study some key food practices in the real field situations (41,42).…”
Section: Participatory Techniques: Combined Approaches With Personal Interviewsmentioning
confidence: 99%